On (u,v) Distinct Congruent Spectrum of Graphs - T. Rajasulochana, M. Kamaraj (Mathematical Statistician and Engineering Applications, 2023)
An (u,v) distinct congruent spectrum of graph G with u vertices and v –edges is an injective mapping from the set of edges to the set of nonnegative integers 1,2,…v in such a way that the set of values of vertices obtained by the sums mod |E(G)| +1 .In this paper certain class of graphs are discussed.